Urban green innovation's spatial association networks in China and their mechanisms. (June 2023) - Dong, Shumin; Ren, Guixiu; Xue, Yuting; Liu, Kai
Highlights: There are significant overall network features in urban green innovation. Urban green innovation's individual network has a core-periphery structure. Urban green innovation is spatially clustered. Abstract: Green innovation is an important concept of sustainable development to achieve resource conservation and environmental optimization. It is of importance to investigate the spatial association networks of urban green innovation (UGI) and their mechanisms in order to expand research on green innovation and develop urban policies. In the present study, green patents are employed to reflect UGI, social network analysis is used to examine the overall networks, individual networks, and blocks of UGI, and a Quadratic Assignment Procedure is employed to verify its mechanisms across 359 Chinese cities. According to the results, China's UGI had significant overall network features, but the spatial association between individual cities still needs to be improved. In Chinese cities, there was a significant polarization of green innovation networks, with a remarkable core-periphery structure. Despite the obvious spatial clustering in China's UGI, the spatial association mostly occurred within blocks, and it is necessary to strengthen the association between blocks. A spatial association network for UGI is more likely to be formed when there is a greater difference in science and technology policy and culture, and a smaller difference in ecological environment and environmental policy.